(untitled) (Journal of Current and Advance Medical Research, 2024)
Background: Several spinal diseases are admitted in the hospital for the management. Objective: The purpose of the present study was to assess the status of patients presented with different spinal pathologies admitted at referral neuroscience hospital in Bangladesh. Methodology: This retrospective cross-sectional study was conducted in the Department of Neurosurgical spine at National Institute of Neurosciences and Hospital, Dhaka, Bangladesh from January 2022 to December 2022 for a period of one year. All the patients with any age presented with spinal complain like pain, movement restriction or bony destruction were selected for this study. The patients with traumatic injury to the spine were excluded from this study. The details of the patients were recorded for this study. The management of the patients were performed according to the treatment protocol of this institute. Results: A total number of 463 patients were admitted in the Department of Neurosurgery Spine during the study period. Among these, 357 cases were treated with surgery and the rest 106 cases were managed under conservative treatment. The mean age group of this study population was 35.2±15.3 years with the age range of 21 to 71 years. The male and female ratio was 1.5:1. Among 463 cases surgery was performed in majority of cases which was 357 cases and the rest of 106 cases were managed by conservative treatment. Most of the spinal cord pathologies were detected in the lumber region which was 251(70.3%) cases. Spinal cord pathologies in cervical region was reported in 69(19.3%) cases. However, others are reported in 37(10.4%) cases. Conclusion: In conclusion the middle age male patients are most commonly presented with the spinal pathologies and the lumber region is the most common site of pathologies. Journal of Current and Advance Medical Research, July 2023;10(2):70-74